PRELIMINARY SURVEY OF THE CURRENT STATUS OF SICK BUILDING SYNDROME IN SELECTED DEPARTMENTS OF HANOI MEDICAL UNIVERSITY HOSPITAL 2026 (Vietnam Journal of Community Medicine, 2026)
Objective: Assessment of the current status of sick building syndrome among healthcare workers in some departments/centers at Hanoi Medical University Hospital 2026.Research methods: A cross-sectional descriptive study was conducted among 132 healthcare workers at Hanoi Medical University Hospital in 2026 with the aim of surveying the prevalence of sick house syndrome through the MM040EA questionnaire.Results: The average closed-door syndrome score was 10.1 ± 4.3. Multivariate regression analysis identified associated factors that increased closed-door syndrome scores, including: high work pressure (β = 4.22; p = 0.043), stuffy air (β = 3.51; p < 0.001), annoying noise (β = 2.46; p = 0.040), poor hygiene (β = 2.24; p = 0.003), female gender (β = 2.05; p = 0.028), and allergy history (β = 1.48; p = 0.041).Conclusion: The prevalence of sick building syndrome at the hospital was at a notable level (10.1 ± 4.3 points), with fatigue and headache being the predominant complaints. Workload pressure and stuffy indoor air were the factors most strongly affecting staff health. Improvements in building ventilation and adjustments to work intensity are necessary to ensure the occupational health and safety of healthcare workers
Keywords: Sick building syndrome, healthcare workers, indoor air quality, workload, occupational health, Hanoi Medical University Hospital.